Servet-i Fünûn romanında trajik durum - Yıldırım, Asiye Çığrı (Bartın Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2018)
Trajik günlük dilde çok acı, kederli olanı anlatmak üzere yaygınlık kazanmış bir kavram olmakla birlikte esasında, felsefi, estetik ve edebi alanda kendine özgü koşulları ifade eder. Trajik kavramının kendine özgü koşulları ise en bariz şekilde Antik Yunan’a ait tragedya metinlerinde görülür. Tragedya metinlerinde trajik, kahramanın, sınırlı özgürlük içinde, yazgısına direnme gücü ve kabiliyetiyle, etik alanda yaşadığı çatışmayı içeren durumdur. Tragedyadan çıkan ve daha geniş anlam alanına sahip olması ile tragedyayı da kapsayan trajik, hayatta var olduğu sürece hayatın yorumundan ibaret olan sanatta da varlığını sürdürür. Bu sanatların başında ise edebiyat gelmektedir. Bir edebi eseri değerlendirmede, ön koşul, kuşkusuz yapıtı anlamaktır. Bu ise ancak insan ilişkilerini, yaşantı ve olanaklarını, özgürlük ve sınırlılık alanlarını; eylemlerin hangi ilkeler üzerinden gerçekleştiğini kavramakla mümkündür. Bu çalışmada, içeriğin kavranmasına sağlayacağı katkı ile metnin daha doğru değerlendirilmesine imkân tanıyacak trajik kavramı tahlil unsuru olarak ele alınmıştır.

Although being a widespread concept to describe a very painful, sad one in daily language, “tragic” in reality expresses its own unique conditions in philosophical, aesthetic, and literary context. The peculiar conditions tragic appear most obviously in the tragedy texts of ancient Greece. Tragic in tragedy texts is a situation in which the hero with the power and ability to resist the fate lives an ethical conflict in the limited freedom of being a human being. Therefore, tragic, which comes from tragedy and at the same time consists of the tragedy due to its coverage of the wider sense of the meaning, continues, as long as it is in our lives, its existence in the art as an interpretation of life. Literature is the primary area of these arts. The precondition for evaluation of a literary work is, of course, understanding the work. This is only possible when one conceives human relations, life and possibilities, freedom and limitations, and which principles establish the basis for actions to take place. In this study, the tragic concept that allows the more accurate evaluation of the text with its contribution to the comprehension of the content is considered as an analysis element. In this thesis, the tragic concept in the introduction part is investigated from a general framework, and its root and meaning are assessed by taking into consideration the definitions in various disciplines. In the conclusion, value conflicts and tragic characters were compared in terms of their similarities and differences in a holistic perspective; moving from tragic, the similarities and differences between novels were determined at the author and period level.
Tez, yazarı tarafından 26.01.2019 tarihine kadar erişime kısıtlanmıştır.
Keywords: Türk romanı; Edebiyat; Türk edebiyatı; Turkish novel; Literature; Turkish literature